2022
DOI: 10.1155/2022/7356943
|View full text |Cite
|
Sign up to set email alerts
|

Photoelectric Performance Optimization of Dye‐Sensitized Solar Cells Based on ZnO‐TiO2 Composite Nanofibers

Abstract: As the electron transport layer of dye-sensitized solar cells (DSSCs), the photoanode is an important component that affects photoelectric conversion efficiency (PCE). The commonly used material titanium dioxide (TiO2) is difficult to prepare as nanostructures with large specific surface area, which affects dye loading and electrolyte diffusion. Herein, TiO2 nanofibers and ZnO-TiO2 composite nanofibers with different molar ratios are synthesized by electrospinning technology. The above nanofibers are coated on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…Additionally, evenly distributed tiny pores due to the electrospinning process have increased the charge transport rate, resulting in higher outputs. The final device exhibited a V OC of 0.58 V, a current density of 10.36 mA cm –2 , and a FF of 0.61 (Figure c) . Moreover, Nien et al observed that Fe 2 O 3 /TiO 2 and g-C 3 N 4 /TiO 2 electrospinning with a double jet to produce a heterogeneous nanofiber composite had improved the PCE up to 4.81%.…”
Section: Electrospinning Implementation For Energy-autonomous Wearabl...mentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, evenly distributed tiny pores due to the electrospinning process have increased the charge transport rate, resulting in higher outputs. The final device exhibited a V OC of 0.58 V, a current density of 10.36 mA cm –2 , and a FF of 0.61 (Figure c) . Moreover, Nien et al observed that Fe 2 O 3 /TiO 2 and g-C 3 N 4 /TiO 2 electrospinning with a double jet to produce a heterogeneous nanofiber composite had improved the PCE up to 4.81%.…”
Section: Electrospinning Implementation For Energy-autonomous Wearabl...mentioning
confidence: 99%
“…Copyright 2020, Royal Society of Chemistry. (c) Current density and voltage plot for ZnO- and TiO 2 -based DSSC devices reprinted with permission under a Creative Commons [CC BY] License from ref ( 163 ). Copyright 2022 The Authors.…”
Section: Electrospinning Implementation For Energy-autonomous Wearabl...mentioning
confidence: 99%
“…16 Nanofibers and nanofiber composites are promising for energy storage and energy applications as well as for a wide range of other applications such as solar cells, medicine, water and air filtration, drug delivery etc., and the surface-to-volume ratio of the nanofibers plays a major role. [17][18][19][20][21][22] A textile-based counter electrode, consisting of PANI coated carbon fabric, with efficacious photovoltaic performance was developed in a study by Motlagh et al for a flexible dye-sensitized solar cell. 23 A high performance CoWO 4 -PANI electrode sample for electrochemical devices and energy storage was developed and investigated in the study by Rajkumar et al 24 Zeolite (ZT) is a tridimensional form of crystalline aluminosilicate and exhibits well-defined micropores and mesopores.…”
Section: Introductionmentioning
confidence: 99%
“…These nanofiber composites produced a homogeneous distribution on SSCs with an efficient conductivity path for the photoelectrons 16 . Nanofibers and nanofiber composites are promising for energy storage and energy applications as well as for a wide range of other applications such as solar cells, medicine, water and air filtration, drug delivery etc., and the surface‐to‐volume ratio of the nanofibers plays a major role 17–22 . A textile‐based counter electrode, consisting of PANI coated carbon fabric, with efficacious photovoltaic performance was developed in a study by Motlagh et al for a flexible dye‐sensitized solar cell 23 .…”
Section: Introductionmentioning
confidence: 99%
“…12 TiO 2 is non-toxic, environmentally friendly, low-cost, and stable. 13 Reactive oxygen species produced by TiO 2 photocatalysis would attack the weak places in the bacterial cell wall, allowing internal components to seep out and then destroy the injured cells, 14 resulting in an antibacterial action. Since then, several investigations on TiO 2 photocatalytic antibacterial performance have been conducted.…”
Section: Introductionmentioning
confidence: 99%